3D biofilm visualization and quantification on granular bioanodes with magnetic resonance imaging. (15th December 2019) - Caizán-Juanarena, Leire; Krug, Julia R.; Vergeldt, Frank J.; Kleijn, J. Mieke; Velders, Aldrik H.; Van As, Henk; Ter Heijne, Annemiek
Abstract: The use of microbial fuel cells (MFCs) for wastewater treatment fits in a circular economy context, as they can produce electricity by the removal of organic matter in the wastewater. Activated carbon (AC) granules are an attractive electrode material for bioanodes in MFCs, as they are cheap and provide electroactive bacteria with a large surface area for attachment. The characterization of biofilm growth on AC granules, however, is challenging due to their high roughness and three-dimensional structure. In this research, we show that 3D magnetic resonance imaging (MRI) can be used to visualize biofilm distribution and determine its volume on irregular-shaped single AC granules in a non-destructive way, while being combined with electrochemical and biomass analyses. Ten AC granules with electroactive biofilm (i.e. granular bioanodes) were collected at different growth stages (3 to 21 days after microbial inoculation) from a multi-anode MFC and T1 -weighted 3D-MRI experiments were performed for three-dimensional biofilm visualization. With time, a more homogeneous biofilm distribution and an increased biofilm thickness could be observed in the 3D-MRI images. Biofilm volumes varied from 0.4 μL (day 4) to 2 μL (day 21) and were linearly correlated (R 2 = 0.9) to the total produced electric charge and total nitrogen content of the granular bioanodes, with values of 66.4 C μL −1 and 17 μg N μL −1, respectively. In future, in situ MRI measurements could be used to monitor biofilm growth and distribution on AC granules. Graphical abstract: Image 1 Highlights: Biofilm visualization on full electrodes is challenging with microscopy techniques. This research used 3D MRI to visualize biofilms on porous carbon granules. 3D MRI allowed for non-destructive determination of biofilm volume and distribution. Biofilm volume was correlated to total produced charge and total nitrogen content.